HLA-B27 and Clinical Features of Acute Anterior Uveitis in Cuba†. (19th December 2012) - Torres, Sylvia; Borges, Sandra; Artiles, Adriana
Abstract: Background : There are few data about the epidemiology of acute anterior uveitis (AAU) from Latin America. In Cuba, the genetic admixture of the population could modify the HLA-B27-AAU association. In this study, the authors compared the distribution of the HLA-B27 allele in patients and controls and described some clinical outcomes. Materials and Methods : The clinical features of patients were collected from their medical records. HLA-B27 genotyping was performed using the polymerase chain reaction. HLA-B27 allele distribution was compared between patients and controls. Results : HLA-B27 allele was present in 55.4% of the patients and 0.87% of the controls. AAU HLA-B27 positivity was associated with males, frequent episodes, and a systemic disease. There is no difference in ocular complications between HLA-B27-positive and -negative patients. Conclusions : Results from this study are similar to data described in other countries. HLA-B27 allele distribution in controls is lower than other reports in Caucasian populations.